Pembuatan Media Gambar Ilustrasi Berbasis Strategi Mnemonik Dan Pendampingan Guru Bahasa Mandarin Dalam Pembelajaran Hanzi Siswa SD Ujung Pandang - Junaeny, Arini; Usman, Misnawaty; Dalle, Ambo; Nahnu, Asmuliyati; Ramadhani, Asti; Haikal, Haikal (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2024)
Abstract. The partner of this program is a primary school called SD Ujung Pandang. The target of this program is to provide illustrative image media based on the mnemonic strategies and assistance to teachers in teaching Hanzi in the Mandarin language class at primary school. The mnemonic strategies used are the pictograph and ideograph techniques. This activity is divided into four stages, namely, observation, preparation, implementation and evaluation. By providing media and showing the procedures for teaching Hanzi based on the mnemonic, teachers and students can effectively learn to remember Hanzi. Keywords: Mnemonic, Mandarin, Hanzi